Clarifying a Circularity Phenomenon in a Circular Economy under the Notion of Potential - Shevchenko, Tetiana; Vavrek, Roman; Danko, Yuriy; Gubanova, Olena; Chovancová, Jana; Mykhailova, Liubov (Problemy Ekorozwoju, 2021)
Turning from linear to circular business model, from cradle-to-grave to cradle-to-cradle and from waste to wealth, the concept of circular economy (CE) has become an important tool to promote sustainable development as it combines economic, environmental and social benefits at a local as well as global scale. In the shift towards CE, examining the CE from the perspective of its potential is crucial for its wider and more effective implementation in the practice. The aim of the paper is to clarify a circularity phenomenon in closed-loop econ-omy under the notion of potential in part of (1) the structural elements, (2) underlying categories and (3) basal properties as a follow-up to the previous studies about managing the circularity potential. The study provides the theoretical framework for understanding circularity potential by developing the circularity potential categorization in order to get a comprehensive picture of what has been done in the past and where efforts are most need today to achieve a progress towards circularity in the future. The basal properties of circularity potential such as integrity, dynamism, territorial affiliation and different strategies compatibility were revealed and discussed for managing the circularity potential. The findings of the paper have ambition to contribute to new metrics development to measure the progress towards zero-waste and CE aimed at identification and monitoring all the possible forms of the circularity potential – opportunities, reserves, available resources, rather than the available resources only that were primarily considered in the past attempts at the operationalisation of circular economy.